High-speed, low-complexity systolic designs of novel iterative division algorithms in GF(2/sup m/) - Wu, Chien-Hsing; Wu, Chien-Ming; Shieh, Ming-Der; Hwang, Yin-Tsung (IEEE transactions on computers, 2004)
We extend the binary algorithm invented by Stein and propose novel iterative division algorithms over GF(2/sup m/) for systolic VLSI realization. While algorithm EBg is a basic prototype with guaranteed convergence in at most 2m - 1 iterations, its variants, algorithms EBd and EBdf, are designed for reduced complexity and fixed critical path delay, respectively. We show that algorithms EBd and EBdf can be mapped to parallel-in parallel-out systolic circuits with low area-time complexities of O(m/sup 2/loglogm) and O(m/sup 2/), respectively. Compared to the systolic designs based on the extended Euclid's algorithm, our circuits exhibit significant speed and area advantages.